STUDY OF WORKLOAD, JOB SATISFACTION AND EMPLOYEE PERFORMANCE IN MEDICAL RECORD INSTALLATION OF LUBUK PAKAM HOSPITAL - Fadlilah Widyaningsih; Lusi Sundari (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2022)
The success of a hospital in carrying out its role in individual health services and public health is determined by professional and quality human resources who have good performance. One of the human resources that plays an important role in achieving this role is the medical record employee who documents the actions given while in the hospital. This study is a qualitative research that aims to explore the relationship between workload and job satisfaction with employee performance. The research was conducted at Grandmed Lubuk Pakam Hospital. The sample was taken by purposive sampling, while the data was collected by conducting interviews, Focus Group Discussion (FGD), observation and document review. The validity of the data in this study was carried out through method triangulation and source triangulation. The results showed that workload and job satisfaction were related to employee performance. Most employees are included in the heavy workload category (60%) while the lowest employee performance is in the quantity aspect of work (70%). Therefore, performance improvement can be done by providing a workload that is in accordance with the abilities and abilities of employees.